Effect of Left Atrial Appendage Closure in Combination With Catheter Ablation on Left Atrial Function for Persistent Atrial Fibrillation - Yang, Jing; Liu, Yue; Feng, Liang; Liu, Mingqing; You, Ling; Liu, Yu; Wu, Jinglan; Zhang, Guangming; Geng, Xue; Xie, Ruiqin (Frontiers in Cardiovascular Medicine, 2021)
Background: A single procedure combining left atrial appendage closure (LAAC) plus catheter ablation (CA) has been proven to be safe and feasible for treating atrial fibrillation (AF). However, the influence of treatment modality on left atrial (LA) function is not thoroughly explained. Objective: We aimed to investigate the changes of LA function in persistent AF patients undergoing concomitant LAAC and CA. Methods: The study population comprised 65 patients who underwent combined AF ablation and Watchman LAAC (combined therapy group) in our center , and 65 participants of the AF simple ablation group who were matched based on sex, age, CHA2DS2-VASc score and HAS-BLED score using propensity score matching. During the one-year follow-up period, two-dimensional echocardiography and speckle tracking echocardiography were performed to assess LA reservoir, conduit, and contractile function. Results: The combined therapy was associated with a significant improvement in the LA reservoir function with increased expansion index and strain indices, including strain and strain rate (SR) during ventricular systole. Conduit function with SR during early ventricular diastole was also improved, as was contractile function with active atrial emptying fraction and SR during atrial systole. Similarly, LA reservoir and contractile function indices all improved continuously during follow-up after catheter ablation alone. At three months follow-up LA reservoir and conduit function with strain indices had a tendency to improve only in the simple procedure group. At one-year follow-up there was no significant difference in either LA volumes or strain indices between the two groups. Conclusion: Both the combined therapy group and the simple ablation group demonstrated significant improvement in LA function. Based upon the fact that LA function was improved in both groups it might be concluded that most of the effects appeared to result from ablation, not LAAC; furthermore the additional LAAC procedure did not affect the improvement of LA function after CA.